Neuroelectrodynamics : understanding the brain language - Aur, Dorian (Biomedical and health research ;, 2010)
The essence of brain function consists in how information is processed, transferred and stored. This book presents the model - the neuroelectrodynamic model (NED) - which describes the intrinsic computational processes by the dynamics and interaction of charges and helps in understanding the mind in computational terms.